Like Us in Sin: A Freudian Reading of Jesus’s Jewishness - Ben-Johanan, Karma (Studies in Christian-Jewish Relations, 2026)
This paper explores the role that a sense of guilt, and in particular Jewish guilt, has played in the theological relationship between Jews and Christians. It does so through uncovering a disparity between the Jewish and the Christian traditions with relation to the intersection between Jesus’s Jewishness and Jesus’s innocence. Using some of the dynamics in Freud’s Moses and Monotheism, I argue that a “classical” Jewish understanding of Jesus as a Jew is essentially bound up with the perception of Jesus as an equal member of a guilty community, that is, as a sinner. This is a perspective that stands in tension with the foundational Christian dogma that Christ, a Jew, was “like us in all things, except for sin.” After discussing this basic tension through a Freudian lens, I turn to analyze the post-Shoah process of Jewish-Christian reconciliation. I argue that there, too, the question of Christ’s innocence, which remains at the heart of the relationship, is renegotiated through the renewed emphasis on Christianity’s own Jewishness, and especially the Jewishness of Christ. Toward the end of my article, I pose questions about the current, post-October 7 moment in the history of Jewish-Christian relations, and its reallocation of those questions of sin, guilt, and Jesus’s Jewish identity.